OPTIMALISASI PENDIDIKAN ANAK DAN MANAJERIAL ADMINISTRASI PKK DESA NGABLAK KECAMATAN SRUMBUNG - Muhamad Khoirul Huda; Fuad Yanuar Akhmad Rifai; Muhammad Sholikhun (Institut Agama Islam Syubbanul Wathon Magelang, 2021)
Education is teaching that aims to develop the abilities that exist in students. However, many schools are currently closed due to the impact of the COVID-19 pandemic. Thus, the first work program carried out was mentoring the student learning process in the Ngablak village. This assistance has the aim of making students able to carry out learning even though schools are closed. The next program is about the management of the Ngablak Village PKK. The existing Human Resources have not been able to contribute to the administration of the organization. Through training in Microsoft Office Word and Excel, the goal is for PKK administration to run well. The method I use is PAR (participatory action research), meaning that this program was created because it needed to be strengthened by information obtained from the village head and not the development of existing activities. This program has had a positive impact on both the children and the administration of the Ngablak Village PKK.